Microplastic and nanoplastic interactions with per- and polyfluoroalkyl substances (PFAS) in soils: a critical review of main findings and knowledge gaps - Pedro Augusto Soares; Guilherme Silva de Souza; Valéria Guimarães Silvestre Rodrigues; Jacqueline Zanin Lima (Environmental Geochemistry and Health, 2026)
Abstract Microplastics (MPs), nanoplastics (NPs), and per- and polyfluoroalkyl substances (PFAS) can enter soils through biosolids, compost, landfill leachate, reclaimed-water irrigation, treated textiles, and industrial releases. However, whether plastic particles modify PFAS fate in terrestrial environments remains uncertain because most evidence derives from simplified laboratory conditions. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework and identified 430 records from Scopus ( n = 208) and Web of Science ( n = 222). After screening, environmental-domain classification, and critical reassessment, 37 original studies were included in a two-level evidence framework comprising eight core soil or soil-relevant studies and 29 complementary mechanistic studies. PFAS–MP/NP interactions depended on polymer composition, particle size and charge, PFAS chain length and functional group, solution chemistry, weathering, organic matter, mineral coatings, and biofilms. Although pristine plastics often showed substantial PFAS adsorption in aqueous systems, their affinity frequently changed after contact with soils or other environmental matrices. Transport studies did not support a universal carrier effect. Plastic particles facilitated PFAS movement under some conditions, retarded it when particle retention dominated, and had little effect when most PFAS remained dissolved. Biological responses were also context-dependent. MPs increased PFAS bioaccumulation and reproductive toxicity in earthworms, while plant and aquatic studies showed both enhanced and reduced uptake or toxicity depending on particle properties and exposure conditions. Overall, the PFAS vector effect of MPs and NPs is conditional rather than universal. Field monitoring, intact-soil experiments, environmentally conditioned particles, realistic concentrations, complete mass balances, and long-term assessments are needed to determine when plastic-mediated processes become environmentally significant.